KOMPENSASI DAN KEPUASAN KERJA KARYAWAN BAGIAN SALES AND MARKETING INDUSTRI OTOMOTIF DI BANDUNG - Hani Gita Ayuningtias; Ferdinal Syahputra; Arif Partono Prasetio (Universitas Kristen Maranatha, 2017)
The automotive industry face intense competition to win the customers’ choice. In doing so, they need to have a powerful sales team to pursue their target. Individual with higher satisfaction in their job will certainly give better contribution to organization. One of the antecedent of job satisfaction is compensation. The aim of the study is to analyze the effect of employee perception on job satisfaction. We use 385 automotive sales department in Bandung as participant. Data was collected using 50 items questionnaire. The Regression analysis with SPSS used to measure the effect of compensation on job satisfaction. The study found the correlation between two variables is 0,614. The effect of compensation on job satisfaction is 0.377. The result proved that compensation still become important factor to build employees’ satisfaction.this is in line with the automotive companys’ policy which always provide bonuses for those who achieve the target and perform. This policy will drive employees to maintain their performance. Then, the positive cycle of rewards, satisfaction, and performance will keep on going.Keywords: Job satisfaction, Compensation, Automotive Industry